There’s No Place like Aztlán: The Quest for Queer Homeland through Re-visionism in Chicana Feminist Autohistorias - Jones, Amanda M (East Carolina University, 2019)
In this thesis, I explore how authors Gloria Anzaldúa, Cherríe Moraga, Helena María Viramontes, Ana Castillo, Alicia Gaspar de Alba, Sandra Cisneros, Lorna Dee Cervantes, Carla Trujillo and Felicia Luna Lemus represent Chicana queer sexual and gender identity through female Mexican religious, historical and mythological figures - which act as archetypes for character, plot, and symbolism - throughout their creative works (poetry, short prose, short stories, plays and novels) according to Chican@ Queer Theory in order to imagine Queer Aztlán. The female Mexican religious, historical and mythological figures that I will analyze are: La Virgen de Guadalupe, La Malinche, La Llorona, La Muerte, La Diosa Hambrienta (or Huixtocihuatl), Cihuacoatl, Chalchiuhtlicue, Cihuateteo, Coyolxauhqui, Atlacoaya, Chantico, Coatlicue, Itzpapalotl, Mictlancihuatl, Tlazolteotl and Xochiquetzal. Foremost, I will examine the authors' use of the Coyolxauhqui imperative conceptualized in Chican@ Queer Theory. The Coyolxauhqui imperative is the idea that Chicana artists are daughters of Coyolxauhqui - the dismembered Aztec warrior goddess - and are thus tasked with re-membering her (as well as other feminine figures within Chicano culture) and themselves by reconstructing their identities and histories through processes of excavation, decolonization, reclamation, re-vision, and renarrativization in their autohistorias (fiction wherein personal experiences and collective experiences are incorporated into narratives that reflect counterhegemonic lived realities). Through my exploration, I will answer the following questions: What are the characteristics of the authors' Queer Aztlán? How do each of the authors' works contribute to the formation of Queer Aztlán through their use of mythological/religious/historical feminine figures? Who is included in (or excluded from) their Queer Aztlán? What is/was/will be the sociocultural significance of their Queer Aztlán?
Keywords: La Virgen de Guadalupe; La Malinche; La Llorona; La Muerte; La Diosa Hambrienta; Huixtocihuatl; Cihuacoatl; Chalchiuhtlicue; Cihuateteo; Coyolxauhqui; Atlacoaya; Chantico; Coatlicue; Itzpapalotl; Mictlancihuatl; Tlazolteotl; Xochiquetzal; Queer Aztlán; Excavation; Decolonization; Reclamation; Re-vision; Renarrativization; Autohistoria; Chicana; Chicano; Chican@; Xicana; Mexican American women authors; Anzaldúa, Gloria. Borderlands; Anzaldúa, Gloria. Gloria Anzaldúa reader; Gaspar de Alba, Alicia, 1958-. Short stories. Selections.; Lemus, Felicia Luna, 1975- .Trace elements of random tea parties; Lemus, Felicia Luna, 1975- . Trace elements of random tea parties; Viramontes, Helena María, 1954- , Their dogs came with them; Castillo, Ana, So far from God; Cisneros, Sandra. Loose woman & Woman Hollering Creek and other stories; Cervantes, Lorna Dee. Ciento; Trujillo, Carla. What night brings; Feminist literature; Mexican American lesbians; Identity (Philosophical concept) in literature; Homosexuality in literature